2010
DOI: 10.1309/ajcprjp39midsgbh
|View full text |Cite
|
Sign up to set email alerts
|

Significance of PGP9.5 Expression in Cancer-Associated Fibroblasts for Prognosis of Colorectal Carcinoma

Abstract: To assess the expression of a cancer-associated fibroblasts (CAFs) marker as an indicator of prognosis, we raised anti-protein gene product 9.5 (PGP9.5) monoclonal antibody against cultured fibroblasts. PGP9.5 expression in cultured normal fibroblasts was increased by transforming growth factor beta stimulation, indicating the phenotypic alteration to activated fibroblast. We immunohistochemically evaluated PGP9.5 expression with the CAFs of 110 colorectal cancer cases under T3 stage. PGP9.5 immunoreactivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Fibroblast proliferation, angiogenesis and nerve in-growth are all important in the healing process47; this is consistent with our findings of increased vascularity and PGP9.5 expression after rotator cuff repair. The immunopositive reactions of some fibroblasts to PGP9.5 is of interest and may relate to a subpopulation of type B synoviocyte-like cells that have been repeatedly seen in the horse48; of note PGP9.5-immunopositivity has previously been demonstrated in the human fibroblasts 49. The increase in the NK-1 and TrkA receptors, seen specifically around vascular structures, points towards the importance of both substance P and NGF in the process of neurovascular ingrowth 50.…”
Section: Discussionmentioning
confidence: 85%
“…Fibroblast proliferation, angiogenesis and nerve in-growth are all important in the healing process47; this is consistent with our findings of increased vascularity and PGP9.5 expression after rotator cuff repair. The immunopositive reactions of some fibroblasts to PGP9.5 is of interest and may relate to a subpopulation of type B synoviocyte-like cells that have been repeatedly seen in the horse48; of note PGP9.5-immunopositivity has previously been demonstrated in the human fibroblasts 49. The increase in the NK-1 and TrkA receptors, seen specifically around vascular structures, points towards the importance of both substance P and NGF in the process of neurovascular ingrowth 50.…”
Section: Discussionmentioning
confidence: 85%
“…44 Data from several in vitro studies and mouse models suggest that UCHL1 acts as an oncogene in cancer pathogenesis. [45][46][47] Furthermore, high expression of UCHL1 in cancerassociated fibroblasts was shown as an independent, negative prognostic factor for overall and recurrence-free survival. 45 Albo et al 48 reported that neurogenesis-in which UCHL1 is a key player-in colorectal cancer is involved in tumor progression and associated with poor outcome.…”
Section: Modern Pathology (2014) 27 906-915mentioning
confidence: 98%
“…[45][46][47] Furthermore, high expression of UCHL1 in cancerassociated fibroblasts was shown as an independent, negative prognostic factor for overall and recurrence-free survival. 45 Albo et al 48 reported that neurogenesis-in which UCHL1 is a key player-in colorectal cancer is involved in tumor progression and associated with poor outcome. In 2008, Mizukami et al 49 proposed that hypomethylation resulting in re-expression of UCHL1 was significantly associated with lymph node metastasis in colorectal cancer.…”
Section: Modern Pathology (2014) 27 906-915mentioning
confidence: 98%
“…UCHL-1 is overexpressed in pancreatic endocrine tumors, as well as in colorectal and lung cancers. This enzyme is a neuroendocrine marker that recognizes and hydrolyzes a peptide bond at the C-terminus of ubiquitin, and remodels synapses by controlling ubiquitin homeostasis [31][32][33]. In the current study, miR-145 provided to suppress cell proliferation and reverse urothelial carcinomas to the pluripotent cells with stem cell features through induction of senescence, then prompted differentiation to multiple lineages such as squamous, glandular and neuroendocrine cells.…”
Section: Discussionmentioning
confidence: 67%